EVALUASI METODE PENGUJIAN ANGKA LEMPENG TOTAL MENGGUNAKAN METODE PETRIFILM AEROBIC COUNT PLATE TERHADAP METODE UJI SNI 01.2332.2006 PADA PRODUK PERIKANAN DI LPPMHP SURABAYA - Hartati, Fadjar Kurnia (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2016)
The study aims to evaluate the testing methods Total Plate Count (ALT) which is easierand faster is Petrifilm Aerobic Plate Count (PAPC) against resistance in TPC testing infishery products, as well as compliance with the Indonesian National Standard (SNI) 012332.3-2006.This study held in Laboratory Quality Control and Testing of FisheryProducts (LPPMHP) Surabaya, East Java. This study three types of cultures breed bacteriaand 24 types of fishery products by using two methods of testing, as the reference test SNI01-2332.3-2006 and in comparison to the PAPC. The results of the test, then analyzedusing statistical calculations to evaluate the suitability of the ISO 4833 test method.Finally, note that ALT testing using PACP in accordance with ISO 01-2332.3-2006 as astandard method of testing, and has a good fit in the ALT test with a sample of fisheryproductsKeywords : total plate count, ISO 4833, petrifilm aerobic count plate, SNI. 01-2332.3-2006